A decision support system for generating optimal raw milk managment strategies in a dairy supply chain - Gül, Burak. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
The main supply of the dairy business, raw milk, is one the most volatile supplies in fast-moving goods businesses since there are many areas that cause complexities. Raw milk has a high supply seasonality that contradicts with the demand; there is a harsh competition for supply that forces long-term contracts and, inventory alternatives are very limited due to perishability. Moreover, the demand is also volatile and highly sensitive to lost sales. Therefore, it is necessary to utilize an optimal mix of supply, production and inventory strategies that takes all of the items described into account; however, such optimization practices are not common and the strategy mix is usually determined by experience and intuition, being likely to provide a suboptimal solution. The goal of this study is to eliminate the trial-and-error methodology of strategy determination process by implementing a mathematical model of the whole raw milk management system and the relevant strategy options as the basis of a Decision Support System (DSS) to automate the strategic raw milk planning process in an actual dairy company. In addition to modeling and optimization, this study focuses on the user interface design in DSS development for practical use by providing an example with incorporating the new generation Microsoft Ribbon interface.
Keywords: Raw milk -- Government policy -- Turkey.; Raw milk -- Safety measures -- Turkey.; Dairy products industry -- Turkey.